Leadership for Equity: Managing Diversity and Inclusion in Multilingual Classrooms - Henáz Shopie; Yusuf Badawi (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study investigates the role of educational leadership in fostering equity and managing diversity within multilingual classroom environments. In response to increasing linguistic and cultural heterogeneity in schools, the research explores how school leaders implement inclusive practices that accommodate the diverse linguistic identities and learning needs of students. Using a qualitative multiple case study approach, data were collected through interviews, classroom observations, and document analysis in selected multilingual secondary schools. The findings reveal that equity-driven leadership is crucial in shaping inclusive school cultures, influencing teacher practices, and improving student engagement. Leaders who demonstrated cultural responsiveness, promoted professional collaboration, and empowered multilingual learners contributed significantly to creating equitable learning environments. However, the study also found inconsistencies in leadership approaches due to varying policy frameworks, institutional capacities, and professional development support. The study concludes by emphasizing the need for targeted leadership training, inclusive policies, and systemic support to enable leaders to manage linguistic diversity effectively and equitably.